Governance-Based SPBE Model Framework Design in Multi-Level Government - Agung Gumilar Saputra; Ika Sartika (International Journal of Artificial Intelligence Research, 2025)
This research aims to develop a governance-based framework model for the implementation of the Electronic-Based Government System (ESG) in Indonesia. Although ESG is a national strategic agenda, its implementation still faces various challenges, such as institutional fragmentation, low interoperability, minimal public participation, and weak adaptation to technological change. Through a qualitative approach with a literature review and conceptual construction, this research formulates four interrelated governance models: the Transparent Digital Governance Framework, the Collaborative ESG Ecosystem Model (CSEM), the Participatory E-Governance Model (PEGM), and the Adaptive ESG Governance Framework (ASGF). Each model is built on the governance principles of transparency, collaboration, participation, and adaptability as a response to structural weaknesses in current ESG practices. The results show that effective and sustainable digital governance requires the synergy of these four principles in an integrated and contextual manner, particularly to bridge the gap between national policy and local implementation.